Primary hepatic malignant triton tumor mimicking hepatocellular carcinoma by demonstrating arterial-phase hypervascularity and subsequent washout on dynamic contrast-enhanced imaging: a case report and literature review - Zhou, Bo; Zhan, Canyang; Tian, Yang; Gao, Zhenzhen; Yan, Sheng (Frontiers in Medicine, 2024)
Background: Malignant Triton tumor (MTT) is a relatively rare subtype of malignant peripheral nerve sheath tumor (MPNST) characterized by rhabdomyosarcoma differentiation. There are no distinct features of MTT, and it is easy to misdiagnose preoperatively. Case presentation: Here, we describe a rare case of primary hepatic MTT in a 56-year-old male who presented with nonspecific abdominal pain for one day. Magnetic resonance imaging and abdominal computed tomography revealed an extremely large mass located in the right liver with intratumoral hemorrhage, arterial-phase hypervascularity and subsequent washout on dynamic contrast-enhanced imaging and the possibility of intrahepatic metastasis. Tumor marker levels revealed only an elevated level of alpha-fetoprotein (AFP: 5304.0 ng/mL). Then, he received transcatheter arterial chemoembolization combined with lenvatinib and pembrolizumab, and he was diagnosed with hepatocellular carcinoma. After 3 months of neoadjuvant therapy, we resected the hepatic cancer and adherent diaphragmatic pleura. MTT was confirmed by postoperative pathology and immunohistochemistry. Conclusion: Despite the preoperative dignosis of hepatocellular carcinoma with a rising serum AFP level, typical CT and MRI findings, histopathology assessment showing MPNST with rhabdomyosarcoma differentiation confirms the diagnosis of primary hepatic MTT.